Government Intervention to Encourage the Increase of Innovation Activities: The Case of Automotive Component Industry - Ricardo Nurzal, Erry; Hastuti, Pudji (The Asian Journal of Technology Management (AJTM), 2009)
The increasingly globalizing and very tight competition in the world market nowadays requires companies to increase their competitiveness to maintain and strengthen their position. One of the efforts has to be taken into consideration by companies is innovating sustainably. Evidence shows that companies characterised by innovation have above-average productivity and become leader in the industry. Firms innovate either to produce technologically new products or services, or to produce technologically improved products or services. To produce technologically new and improved products or services, firms need to undertake some innovation activities. Innovation activities are all those scientific, technological, organizational, financial and commercial steps, including investment in new knowledge, which actually, or are intended to, lead to the implementation of technologically new or improved products or processes. Small and medium enterprises face some problems to innovate. Government. intervention is needed to manage the problems, and is expected to increase innovation in the industry.Innovation activities discussed in this paper are focused on those occurred in small and medium enterprises in the automotive component sector as one of the sectors will be developed by the government. In the first part is the introduction which presents problem background. Then, the explanation about methodology and followed by the purpose of the study. The next part is results and discussion. Finally, the paper provides recommendation on intervention necessarily to be taken by the government in order to increase innovation activities in the industry.Key words: Government Intervention, Innovation Activities, and Automotive Component Industry